Response to Five Types of Eggplant and Organic Fertilizer Application on Coastal Land - Wenny Panjaitan; Sumardi Sumardi; Yudhi Harini Baertham (University of Prof. Dr. Hazairin, SH, 2022)
Utilization of marginal land such as coastal land is an effort to increase the availability of land for lowland vegetable production such as eggplant. The nature of coastal land that is too porous and poor in nutrients requires action to improve the physical, chemical and biological properties of the soil. The development of suitable types of eggplant in coastal areas is an important step to obtain good growth and yields. This study aims to evaluate the response of five types of eggplant and the application of organic fertilizer on coastal land. The experiment was conducted using a completely randomized block design with three replications. The types that were continuously evaluated were JTY variety, Mustang F1 variety, Kenari variety, Ratih Hijau variety, and SS 201 variety. Application of organic fertilizer used doses of 0 tons/ha, 10 tons/ha and 20 tons/ha. The results showed that there was no interaction between the type of eggplant and the dose of organic fertilizer application on the growth and yield of eggplant on coastal land. The Mustang F1 variety provides the best growth and yields. The application of organic matter at a dose of 20 tons/ha is the best for the growth and yield of eggplant in coastal areas.